Penggunaan Model Pembelajaran Kooperatif Tipe Make A Match untuk Meningkatkan Hasil Belajar Biologi Siswa - Putri Rahayu, Yera (Bedelau: Journal of Education and Learning, 2022)
Abstrak The purpose of writing action research is to find out whether the cooperative learning model of Make A Match type can improve students' biology learning outcomes. biology learning outcomes of students. This research was conducted at SMA Negeri 1 Pinggir in class XI class with the students' ability for biology lessons is quite low. Method The data analysis method used descriptive qualitative method. The result of the research The results obtained were that the Make A Match type cooperative learning model can improve students' biology learning outcomes. This is evident from the results obtained obtained before PTK reached an average of 70 with classical completeness of 61.76%. In cycle 1, the class average score was 74.01 with classical completeness of 82.76%. with classical completeness of 82.35%. While in cycle 2 the average 77.96 with 32 out of 34 students and classical completeness of 94.12%. classical completeness of 94.12%. Conclusion obtained from this research is that the Make a Match type cooperative learning model can improve biology learning outcomes. a Match cooperative learning model can improve the biology learning outcomes of SMA Negeri 1 Pinggir students. Keyword : Model Cooperative Type Make A Match,Biology Student Learning Outcomes Abstrak Tujuan penulisan penelitian tindakan dilakukan untuk mengetahui apakah model pembelajaran kooperatif tipe Make A Match dapat meningkatkan hasil belajar biologi siswa. Penelitian ini dilaksanakan di SMA Negeri 1 Pinggir pada kelas XI dengan kemampuan siswanya untuk pelajaran biologi cukup rendah. Metode pengumpulan datanya pada penelitian ini adalah tes hasil belajar siswa. Metode analisis datanya menggunakan metode deskriptif kualitatif. Hasil penelitian yang diperoleh adalah model pembelajaran kooperatif tipe Make A Match dapat meningkatkan hasil belajar biologi siswa. Hal ini terbukti dari hasil yang diperoleh pada sebelum PTK mencapai rata – rata 70 dengan ketuntasan klasikal 61,76%. Pada siklus 1 didapatkan nilai rata – rata kelas 74,01 dengan ketuntasan klasikal sebesar 82,35%. Sedangkan pada siklus 2 rata – rata nilai siswa 77,96 dengan 32 siswa yang tuntas dari 34 siswa dan ketuntasan klasikal sebesar 94,12%. Kesimpulan yang diperoleh dari penelitian ini adalah model pembelajaran kooperatif tipe Make a Match dapat meningkatkan Hasil Belajar biologi siswa SMA Negeri 1 Pinggir. Kata kunci : Model Pembelajaran Kooperatif tipe Make A Match, Hasil Belajar Biologi Siswa